Neurodevelopmental Trajectories and Clinical Profiles in a Sample of Children and Adolescents With Early- and Very-Early-Onset Schizophrenia - Pontillo, Maria; Averna, Roberto; Tata, Maria Cristina; Chieppa, Fabrizia; Pucciarini, Maria Laura; Vicari, Stefano (Frontiers in Psychiatry, 2021)
Schizophrenia before 18 years is usually divided into two groups. Early-onset schizophrenia (EOS) has an onset between 13 and 17 years of age, whereas Very Early Onset Schizophrenia (VEOS) has an onset at 12 years or before. Previous studies have proven that neurodevelopmental difficulties in social, motor, and linguistic domains are commonly observed in VEOS/EOS. Also, recent research showed a high prevalence of neurodevelopmental disorders (e.g., intellectual disabilities, communication disorders, autism spectrum disorder and neurodevelopmental motor disorders) in VEOS/EOS and indicated genetic overlap between these conditions. These findings supported the model of a neurodevelopmental continuum in which childhood neurodevelopmental difficulties or neurodevelopmental disorders and psychiatric disorders (e.g., schizophrenia) could be conceptualized as an etiological and neurodevelopmental continuum, rather than be considered as discrete entities. Based on this literature, this study aimed to investigate, in a large sample (N=230) of children and adolescents with VEOS/EOS, the relationship between the presence of neurodevelopmental disorders based on DSM-5 criteria or neurodevelopmental difficulties and age, clinical profile (e.g., positive, negative and disorganized symptoms) and global, social and role functioning at the psychotic onset. Our findings showed that, in children and adolescents with neurodevelopmental disorder or neurodevelopmental difficulties, psychotic onset occurs at an earlier age, could be associated to more severe functional impairment (e.g., global, social, role) and characteristics symptoms could be positive symptoms (e.g., grandiose idea, perceptual abnormalities, disorganized communication) and disorganized symptoms (e.g., odd behavior of appearance, bizarre thinking). Instead, in children and adolescents without neurodevelopmental disorder or neurodevelopmental difficulties, psychotic onset could be characterized mainly by the presence of negative symptomatology (e.g., social anhedonia, avolition, expression of emotion, experience of emotions and self and ideational richness). Given these differences, the presence of neurodevelopmental disorder or difficulties should therefore be carefully investigated and considered in planning assessment and treatment of VEOS/EOS.